(untitled) (International journal of artificial intelligence, 2025)
This article discusses the role of psychological states in the formation and strengthening of psychological stability necessary for the successful performance of athletes. Emotional states experienced by athletes before, during and after the competition, psychological factors such as stress, fear, and insecurity directly affect their physical potential and results. Therefore, within the framework of sports psychology, the psychological preparation of athletes, methods for ensuring emotional and volitional stability, self-management techniques, and the effectiveness of motivational approaches are analyzed. The article also contains practical recommendations for sports psychologists, coaches, and athletes themselves.